Thrombosis and Coagulopathy in COVID-19: Current Understanding and Implications for Antithrombotic Treatment in Patients Treated With Percutaneous Coronary Intervention - Liu, Hangkuan; Wang, Zhijia; Sun, Haonan; Teng, Tianming; Li, Yongle; Zhou, Xin; Yang, Qing (Frontiers in Cardiovascular Medicine, 2021)
As Corona Virus Disease 2019 (COVID-19) has already become a global pandemic, there is an urgent to deepen our understanding of the pathogenesis underlying this disease. Evidence from clinical observations and autopsy studies has demonstrated a complex chain of events proceeding COVID-19 related death, which is temporally characterized by endothelial dysfunction, platelet activation, thrombosis, coagulopathy, and multiple organ failure. Globally, millions of patients with coronary heart disease underwent percutaneous coronary intervention (PCI) each year, with ensuring intensified antithrombotic treatment, i.e., dual antiplatelet therapy (DAPT), for at least 6 months post PCI. Considering the dynamic changes of platelet counts and activation status during the development of CIVID-19, it is a global challenge for clinicians to reduce the ischemic events following stent implantation while without causing bleeding complications in patients following PCI complicated by COVID-19. This review summarized recent progress underlying COVID-19 related platelet changes, both in activation status and in quantity, which may provide a mechanistic basis for the clinicians to make decisions concerning the pros and cons of DAPT in this clinical scenario.